Making sense of students’ errors in solving problems related to measures of dispersion - Ng Chiew Leng; Chew Cheng Meng (Institute of Advanced Engineering and Science, 2023)
The importance of statistical learning has been widely discussed. However, little effort has been made to understand the difficulties of students in learning measure of dispersion, which is the key component to statistical learning. The present study sought to identify the reasons behind the errors committed in solving problems related to measures of dispersion, by examining students’ errors in the diagnostics tests, followed by in depth interviews to elicit their thinking and understanding. There were 85 grade-11 high school students involved in the first phase of the quantitative research and 10 students with weak performance were subsequently selected for the second phase qualitative research. The interviews were conducted using the contingent teaching model. The findings indicated that students’ committing errors in solving problems related to measure of dispersion due to lacking statistical vocabulary knowledge, weak symbol sense, rote learning, low statistical reasoning and statistical thinking ability. The results of the study and proper remedials are discussed.